The Impact of Corporate Responsibility (CSR) of Pt. Pltu Paiton on Non-Governmental Groups in Realizing Social Economic Independence - rika Aprilia (IJED: International Journal of Economy Development Research, 2025)
Corporate Social Responsibility (CSR) is one of the company's strategies in making a positive contribution to the surrounding community. PT. PLTU Paiton has implemented various CSR programs that focus on empowering Non-Governmental Groups (KSM) to increase local economic independence in Probolinggo Regency. This study aims to analyze the impact of PT. Paiton coal-fired power plant to KSM and the extent to which this program contributes to building the economic welfare of the community. The method used is qualitative, with a case study approach and in-depth interviews with KSM members and related stakeholders. The results of the study show that PT. PLTU Paiton has had a positive impact on increasing the capacity of KSM in managing businesses based on local wisdom. In addition, the sustainability of CSR programs also contributes to increasing the economic competitiveness of the community in the agribusiness and tourism sectors. The main success factor in the implementation of this program is the synergy between companies, local governments, and communities in building a sustainable economic ecosystem. This research provides recommendations for companies to continue to develop CSR programs by considering sustainability aspects and active community participation